How the Charter Has Failed Non-citizens in Canada: Reviewing Thirty Years of Supreme Court of Canada Jurisprudence - Dauvergne, Catherine (McGill Law Journal / Revue de droit de McGill, 2013)
This article reviews the Supreme Court of Canada’s treatment of claims by non-citizens since the introduction of the Canadian Charter of Rights and Freedoms. While the early decisions in Singh and Andrews were strongly supportive of rights for non-citizens, the subsequent jurisprudence has been strikingly disappointing. This study shows that the decline in rights protections for non-citizens is a predictable consequence of some of the Court’s early interpretative positions about the Charter. This study considers all Supreme Court of Canada decisions in the thirty-year time frame. The analysis is rounded out by a consideration of cases that were not granted leave and cases that engage directly with an issue of non-citizens’ rights even where a non-citizen was not a party. The concluding section shows that non-citizens in Canada now have less access to rights protections than do non-citizens in some key comparator countries.